Print Works by the Japanese Contemporary Artists. (Tokyo : The Japan Foundation, 1990)
Shusaku Arakawa ; Naoyoshi Hikosaka ; Kousai Hori ; Arinori Ichihara ; Shouichi Ida ; Mitsuo Kanou ; Tatsuo Kawaguchi ; Noriko Kiyozuka ; Akira Komoto ; Yayoi Kusama ; Lee U-Fan ; Hiromitsu Morimoto ; etc.
Print Works by the Japanese Contemporary Artists, The Japan Foundation, Tokyo, 1990
boek
Keywords: Japan